Foliar-applied boron improves flag leaf reserves translocation, pollen viability and yield of aromatic monsoon rice - Rana, Sayed Sajeeb; Islam, M Rafiqul; Bari, Md Nasimul; Mia, M A Baset; Rahman, Md Zillur (Fundamental and Applied Agriculture, 2021)
The planting of monsoon rice (locally known as aman rice) may be delayed due to late heavy rainfall in many regions of South and Southeast Asia resulting in high spikelet sterility with substantial yield loss due to low temperatures during the reproductive stage. Therefore, the study evaluated the performance of foliar-applied boron in mitigating that problem towards sustainable aman rice production. A field experiment was laid out in a randomized complete block design where different levels of boron viz. 0, 50, 100, 150, 200, and 250 ppm were foliar-sprayed at 33 and 47 days after transplanting (DAT) to a popular aromatic rice cultivar Kataribhog grown in late monsoon. Data were collected on phenology, SPAD value at variable dates, pollen viability, boron concentration in leaves and grains, and yield traits and yield. The pollen viability increased by 81.6% for 200 ppm boron. Boron decreased flag leaf weight but increased panicle weight. Simultane- ously, it decreased flag leaf SPAD value and subsequent increase in grain yield, which indicates profound flag leaf reserves translocation into the grain. Foliar-applied B at 200 ppm showed a 32.4 and 40.9% increase of B in leaf and grain, respectively, and improved yield attributes resulting in increased grain yield by 47.0%. The grain yield had strong positive relations with the B content in leaf and grain, and yield contributing characters. The results con- clude that foliar-applied appropriate dose of B can reduce spikelet sterility, individual grain weight and eventually enhance grain formation towards increasing yield in late sown aromatic monsoon rice.